Conductive copper paste and preparation method and application thereof

By adjusting the copper slurry formula, using spherical copper powder and sheet copper powder with a specific weight ratio, and using vapor phase silica and rosin resin additives, the problems of bubbles and edge cracking of multi-layer ceramic capacitors during sintering are solved, achieving good density and improvement of the copper ends.

CN115083655BActive Publication Date: 2025-04-25德阳三环科技有限公司 +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210694555.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-17
Publication Date
2025-04-25
Estimated Expiration
2042-06-17

AI Technical Summary

Technical Problem

The existing multi-layer ceramic capacitors are bubbled on the side or top when the copper slurry end is sintered due to gas failure to discharge in time, and the edge cracking is caused by excessive shrinkage between the edge copper powder during sintering.

Method used

By adjusting the copper slurry formula, the specific weight ratio of spherical copper powder and sheet copper powder (1.8~2.5) is used, and the particle size is controlled. The gas-phase silica and rosin resin are used as additives to delay the degree of sintering and densification of the copper end, ensure the unobstructed gas discharge channel, and inhibit edge cracking.

Benefits of technology

On the premise of ensuring the tightness of the copper end, the problems of bubbles and edge cracking are effectively solved, and the appearance quality and reliability of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003699889300000121
    Figure BDA0003699889300000121
  • Figure BDA0003699889300000131
    Figure BDA0003699889300000131
Patent Text Reader

Abstract

The present invention discloses a conductive copper paste and a preparation method and application thereof, belonging to the technical field of electronic materials. The conductive copper paste comprises the following components in percentage by weight: 55-79% conductive phase, 10-35% organic phase, 5-15% glass phase, and 0.2-1.5% auxiliary agent; the conductive phase comprises spherical copper powder and flaky copper powder, and the weight ratio of the spherical copper powder to the flaky copper powder is spherical copper powder: flaky copper powder = 1.8-2.5. The conductive copper paste solves the problem of bubbling on the side or top of the copper paste end due to the failure to discharge gas in time during sintering, and the appearance problem of cracking of the edge due to excessive sintering shrinkage between the edge copper powders during sintering, while ensuring good density of the copper end.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic materials, and in particular to a conductive copper paste and a preparation method and application thereof. Background Art

[0002] Multilayer ceramic capacitors are one of the most widely used and fastest growing chip components in the world. It is a surface-mounted multilayer ceramic capacitor component made by alternating dielectrics and electrodes. It is used in digital products such as televisions, mobile phones, computers, medical devices, and video recorders. It is widely used in coupling, filtering, oscillation, and bypass circuits in electronic complete machines of industrial automation control equipment. Existing multilayer ceramic capacitors include multiple stacked dielectric layers, internal electrodes that are arranged relative to each other and have dielectric layers between them, and external electrodes that are electrically connected to the internal electrodes. The external electrode structure includes three metal layers of Cu, Ni, and Sn from the inside to the outside. The copper layer is mainly made by the process of applying copper paste and end firing. Therefore, the performance of the copper paste has an important influence on the appearance, basic electrical properties, reliability, and solder resistance of the capacitor.

[0003] The existing copper paste has bubbling problems on the sides or top due to the failure to discharge gas in time during sintering, and appearance problems of edge cracking due to excessive sintering shrinkage between copper powders at the edges during sintering. The causes of these problems are relatively complicated. The copper sintering process, termination process, drying process, copper paste formula, etc. in actual production are all important influencing factors of bubbling and edge cracking, especially the copper paste formula has the greatest impact. If there is a problem with the copper paste formula, it will leave a very narrow process window for the subsequent process flow, which will cause serious quality problems in actual production.

[0004] CN113724912A discloses a high sintering density copper paste for MLCC and a preparation method thereof, which further discloses that the components in the copper paste formula are as follows by mass percentage: 40-60% of first copper powder; 10-30% of second copper powder; 3-5% of first glass powder; 0.5-2.5% of second glass powder; 20-25% of organic carrier; and 0.5-3% of auxiliary agent; wherein the first copper powder and the second copper powder are spherical copper powders, and the average particle size of the first copper powder is larger than the average particle size of the second copper powder. By selecting a suitable type of copper powder, the density of the sintered rear end electrode is improved, but it cannot solve the bubbling problem on the side or top and the appearance problem of edge cracking caused by excessive sintering shrinkage between the edge copper powders during sintering.

[0005] Therefore, how to improve the bubbling and / or edge cracking problems on the side or top by adjusting the copper slurry formula has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0006] The object of the present invention is to overcome the shortcomings of the prior art and provide a conductive copper paste and a preparation method and application thereof. The conductive copper paste solves the problem of bubbling on the side or top of the copper paste end due to the failure to discharge gas in time during sintering, and the appearance problem of cracking at the edge due to excessive sintering shrinkage between copper powder at the edge during sintering, while ensuring good density of the copper end.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A conductive copper paste comprises the following components in percentage by weight: 55-79% conductive phase, 10-35% organic phase, 5-15% glass phase, and 0.2-1.5% auxiliary agent;

[0009] The conductive phase includes spherical copper powder and flaky copper powder, and the weight ratio of the spherical copper powder to the flaky copper powder is spherical copper powder:flaky copper powder=1.8-2.5.

[0010] The inventors of the present invention have found in a large number of studies on conductive copper pastes that, under the above-mentioned specific combination of raw materials in percentage by weight, by adding spherical copper powder and flake copper powder in the specific weight ratio of 1.8 to 2.5, the problem of bubbling on the side or top of the copper paste end due to the failure to discharge gas in time during sintering, and the appearance problem of cracking at the edge due to excessive sintering shrinkage between the edge copper powders during sintering are solved while ensuring good density of the copper end.

[0011] The inventors have found that the weight ratio of the spherical copper powder and the flaky copper powder is the key to the appearance of bubbling problems on the side or top and cracking of the edges. If the weight ratio of the spherical copper powder and the flaky copper powder is lower than 1.8, the sintering activity of the copper powder is too high, which can easily cause bubbling at the top or side of the copper end, or leave a relatively narrow process window for the subsequent termination process and copper burning process. At the same time, the sintering shrinkage of the copper slurry at the edges will be aggravated, resulting in cracking of the edges after sintering. If the weight ratio of the spherical copper powder and the flaky copper powder is greater than 2.5, the sintering activity of the copper slurry is low, the density of the copper end is poor, and a relatively narrow process window is left for the subsequent termination process and copper burning process, which can easily cause density fluctuations. Therefore, it is necessary to strictly control the weight ratio of the spherical copper powder and the flaky copper powder within the range of 1.8 to 2.5.

[0012] The inventors further investigated the effect of the raw material ratio in the conductive copper powder on the bubbling problem on the side or top, the appearance problem of cracked edges, and the density, and found that if the weight percentage is not within the above range, either the density is poor, or there will be bubbling problems on the side or top and / or the appearance problem of cracked edges. Therefore, the weight percentage needs to be strictly controlled within the above range.

[0013] As a preferred embodiment of the present invention, the conductive copper paste comprises the following components in weight percentage: 65-75% conductive phase, 16-24% organic phase, 8-10% glass phase, and 0.5-1% additive. In particular, within the above weight ratio range, it is possible to better solve the bubbling problem on the side or top of the copper paste due to the failure to discharge the gas in time during sintering, and the appearance problem of cracking of the edge due to excessive sintering shrinkage between the edge copper powders during sintering.

[0014] As a preferred embodiment of the present invention, the weight ratio of the spherical copper powder to the flake copper powder is 1.8 to 2.2. In particular, when the weight ratio of the spherical copper powder to the flake copper powder is 1.8 to 2.2, it can better solve the bubbling problem on the side or top due to the failure to discharge the gas in time during the sintering of the copper slurry end, and the appearance problem of cracking of the edge due to the excessive sintering shrinkage between the edge copper powders during sintering.

[0015] As a preferred embodiment of the present invention, the average particle size of the spherical copper powder is 2 to 5 μm, and the average particle size of the flake copper powder is 4 to 9 μm.

[0016] Compared with the spherical copper powder, the flaky copper powder has a larger specific surface area, the activity of the oxidation reaction is improved during the heating process, and the softened glass component and the copper powder are better infiltrated, thereby promoting the entire liquid phase sintering process. Compared with using spherical copper powder alone, the copper end density is better under the same sintering process.

[0017] In the early stage of the entire sintering process, the densification of the copper end and the discharge of the product gases of organic decomposition, carbon oxidation gas, sulfur dioxide, etc. are carried out simultaneously. If the densification of the copper end is completed too early, it will affect the discharge of the above-mentioned gases, which will easily cause bubbling. Therefore, it is necessary to delay the sintering densification degree of the copper end to ensure sufficient time for the gas discharge channel to be unobstructed. The present invention can effectively delay the sintering densification degree of the copper end by selecting the above-mentioned specific weight ratio of spherical copper powder and flaky copper powder and controlling their particle size, thereby ensuring sufficient time for the gas discharge channel to be unobstructed and avoiding bubbling.

[0018] In MLCC products, copper paste covers the top and both sides of the porcelain body. During the sintering process, there will be stress caused by sintering shrinkage in opposite directions at the edges of the top and sides. If the stress is too large, the copper coverage will be lost at this place, causing the edges to crack. The proportion of flaky copper powder in the entire copper powder can greatly affect the shrinkage of the edges. Due to the morphology, the sintering shrinkage of flaky copper powder is much smaller than that of spherical copper powder within the current particle size range. By selecting the above-mentioned specific weight ratio of spherical copper powder and flaky copper powder and controlling their particle size, the edge cracking caused by severe shrinkage of the copper end during the sintering process can be suppressed.

[0019] As a preferred embodiment of the present invention, the auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=0.5-2.

[0020] The present invention selects fumed silica and rosin resin as auxiliary agents. The fumed silica is used as a good thixotropic agent, which can make the slurry have a good shape and termination characteristics, and ensure the good appearance of the product. In addition, compared with other organic thixotropic agents, the inorganic fumed silica does not increase the burden of glue removal, and effectively reduces the risk of product bubbling. The surface of the rosin resin contains a large number of active functional groups, which can effectively improve the adhesion of the slurry, prevent the copper from falling off during the transportation process of the product, and improve the qualified rate of product appearance. The fumed silica and the rosin resin are used together to play a good synergistic effect, which is better than the single use of fumed silica and / or rosin resin.

[0021] As a preferred embodiment of the present invention, the glass phase is at least one of Ba-Si-Zn glass powder, Ba-Zn glass powder, and Si-Zn glass powder. Preferably, the glass phase has a softening point of 450-600°C and a particle size D50 of 1-3 μm. Selecting the glass phase described above can ensure good bonding between the copper end and the porcelain body and the compactness of the copper end.

[0022] As a preferred embodiment of the present invention, the organic phase comprises resin and solvent, and the weight ratio of the resin to the solvent is resin:solvent=0.3-0.6.

[0023] As a preferred embodiment of the present invention, the resin is at least one of acrylic resin, methyl cellulose, ethyl cellulose, polyvinyl butyral, and phenolic resin, preferably acrylic resin.

[0024] As a preferred embodiment of the present invention, the solvent is at least one of terpineol, dihydroterpineol and dihydroterpineol acetate, preferably terpineol.

[0025] The present invention also provides a method for preparing a conductive copper paste, comprising the following steps:

[0026] The conductive phase, the organic phase, the glass phase and the additive are mixed evenly and sieved to obtain a conductive copper paste.

[0027] The present invention also provides an application of the above-mentioned conductive copper paste in a multilayer ceramic capacitor.

[0028] The beneficial effects of the present invention are as follows: (1) The conductive copper paste of the present invention solves the problem of bubbling on the side or top of the copper paste end due to the failure to discharge gas in time during sintering, and the appearance problem of cracking at the edge due to excessive sintering shrinkage between copper powder at the edge during sintering, while ensuring good density of the copper end. (2) The present invention can effectively delay the sintering densification degree of the copper end by selecting the spherical copper powder and the flaky copper powder in the above-mentioned specific weight ratio and controlling their particle size, thereby ensuring sufficient time for the gas exhaust channel to be unobstructed, avoiding bubbling, and inhibiting the edge cracking caused by severe shrinkage of the copper end during the sintering process; (3) The present invention can select fumed silica and rosin resin as auxiliary agents. Fumed silica is a good thixotropic agent, which can make the slurry have good shape and termination characteristics, ensuring a good appearance of the product. In addition, compared with other organic thixotropic agents, inorganic fumed silica does not increase the burden of binder removal, effectively reducing the risk of product bubbling; the surface of rosin resin contains a large number of active functional groups, which can effectively improve the adhesion of the slurry, prevent the product from losing copper during transportation, and improve the product appearance qualification rate. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The preparation methods of the conductive copper paste described in the present invention and the embodiments are: premixing the resin and the solvent to obtain an organic phase, uniformly mixing the conductive phase, the organic phase, the glass phase and the additive, and passing through a 300-mesh sieve to obtain the conductive copper paste.

[0031] Example 1

[0032] A conductive copper paste comprises the following components in percentage by weight: 55% conductive phase, 34% organic phase, 10% glass phase and 1% auxiliary agent.

[0033] The conductive phase includes spherical copper powder and flake copper powder, the weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder = 2; the average particle size of the spherical copper powder is 3 μm, and the average particle size of the flake copper powder is 5 μm.

[0034] The auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=1.

[0035] The glass phase has a softening point of 600° C. and a particle size D50 of 3 μm. The Ba-Si-Zn glass powder comprises the following components in percentage by weight: 45% BaO, 7% SiO 2 、10% ZnO、20% B 2 O 3 ,1%CuO,1%SrO,10%Al 2 O 3 , 6%CaO.

[0036] The organic phase includes acrylic resin and pineol, and the weight ratio of the acrylic resin to pineol is acrylic resin:pineol=0.4.

[0037] Example 2

[0038] The difference between Example 2 and Example 1 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0039] A conductive copper paste comprises the following components in percentage by weight: 60% conductive phase, 29% organic phase, 10% glass phase and 1% auxiliary agent.

[0040] Example 3

[0041] The difference between Example 3 and Example 1 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0042] A conductive copper paste comprises the following components in percentage by weight: 65% conductive phase, 24% organic phase, 10% glass phase and 1% auxiliary agent.

[0043] Example 4

[0044] The difference between Example 4 and Example 1 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0045] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 16% organic phase, 10% glass phase and 1% auxiliary agent.

[0046] Example 5

[0047] The difference between Example 5 and Example 1 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0048] A conductive copper paste comprises the following components in percentage by weight: 75% conductive phase, 14% organic phase, 10% glass phase and 1% auxiliary agent.

[0049] Example 6

[0050] The difference between Example 6 and Example 1 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0051] A conductive copper paste comprises the following components in percentage by weight: 79% conductive phase, 10% organic phase, 10% glass phase and 1% auxiliary agent.

[0052] Example 7

[0053] The difference between Example 7 and Example 5 is that the weight ratio of the spherical copper powder and the flake copper powder is different, and the other parts are the same.

[0054] The weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder=1.8.

[0055] Example 8

[0056] The difference between Example 8 and Example 5 is that the weight ratio of the spherical copper powder and the flake copper powder is different, and the other parts are the same.

[0057] The weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder=2.2.

[0058] Example 9

[0059] The difference between Example 9 and Example 5 is that the weight ratio of the spherical copper powder and the flake copper powder is different, and the other parts are the same.

[0060] The weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder=2.5.

[0061] Example 10

[0062] The difference between Example 10 and Example 4 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0063] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 16.8% organic phase, 10% glass phase and 0.2% auxiliary agent.

[0064] Embodiment 11

[0065] The difference between Example 11 and Example 4 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0066] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 16.5% organic phase, 10% glass phase and 0.5% auxiliary agent.

[0067] Example 12

[0068] The difference between Example 12 and Example 4 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0069] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 16.2% organic phase, 10% glass phase and 0.8% auxiliary agent.

[0070] Embodiment 13

[0071] The difference between Example 13 and Example 4 is that the raw material ratio of the conductive copper paste is different, and the other parts are the same.

[0072] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 15.5% organic phase, 10% glass phase and 1.5% auxiliary agent.

[0073] Embodiment 14

[0074] The difference between Example 14 and Example 4 is that the ratio of fumed silica and rosin resin in the auxiliary agent is different, and the other parts are the same.

[0075] The auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=0.5.

[0076] Embodiment 15

[0077] The difference between Example 15 and Example 4 is that the ratio of fumed silica and rosin resin in the auxiliary agent is different, and the other parts are the same.

[0078] The auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=1.3.

[0079] Example 16

[0080] The difference between Example 16 and Example 4 is that the ratio of fumed silica and rosin resin in the auxiliary agent is different, and the other parts are the same.

[0081] The auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=2.

[0082] Comparative Example 1

[0083] The difference between Comparative Example 1 and Example 4 is that the weight ratio of the spherical copper powder and the flake copper powder in Comparative Example 1 is different, and the weight ratio is not within the scope of the present invention, and the others are the same.

[0084] The weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder=1.5.

[0085] Comparative Example 2

[0086] The difference between Comparative Example 1 and Example 4 is that the weight ratio of the spherical copper powder and the flake copper powder described in Comparative Example 2 is different, and the weight ratio is not within the scope of the present invention, and the others are the same.

[0087] The weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder=3.

[0088] Comparative Example 3

[0089] The difference between Comparative Example 3 and Example 4 is that the conductive phase of Comparative Example 3 is a single spherical copper powder, and the other aspects are the same.

[0090] Comparative Example 4

[0091] The difference between Comparative Example 4 and Example 4 is that the conductive phase of Comparative Example 4 is a single flaky copper powder, and the other aspects are the same.

[0092] Comparative Example 5

[0093] The difference between Comparative Example 5 and Example 4 is that the ratio of the conductive copper paste described in Comparative Example 5 is different from that in Example 4, and its ratio is not within the scope of the present invention, and the others are the same.

[0094] A conductive copper paste comprises the following components in percentage by weight: 50% conductive phase, 35% organic phase, 14% glass phase and 1% auxiliary agent.

[0095] Comparative Example 6

[0096] The difference between Comparative Example 6 and Example 4 is that the ratio of the conductive copper paste described in Comparative Example 6 is different from that in Example 4, and its ratio is not within the scope of the present invention, and the others are the same.

[0097] A conductive copper paste comprises the following components in percentage by weight: 84% conductive phase, 10% organic phase, 5% glass phase and 1% auxiliary agent.

[0098] Comparative Example 7

[0099] The difference between Comparative Example 7 and Example 4 is that the conductive copper paste described in Comparative Example 7 does not contain an additive, and the other aspects are the same.

[0100] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 17% organic phase, 10% glass phase and 0% auxiliary agent.

[0101] Comparative Example 8

[0102] The difference between Comparative Example 8 and Example 4 is that the content of the auxiliary agent in the conductive copper paste described in Comparative Example 8 is not within the scope of the present invention, and the others are the same.

[0103] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 16.9% organic phase, 10% glass phase and 0.1% auxiliary agent.

[0104] Comparative Example 9

[0105] The difference between Comparative Example 9 and Example 4 is that the content of the auxiliary agent in the conductive copper paste described in Comparative Example 9 is not within the scope of the present invention, and the others are the same.

[0106] A conductive copper paste comprises the following components in percentage by weight: 73% conductive phase, 15% organic phase, 10% glass phase and 2% auxiliary agent.

[0107] Comparative Example 10

[0108] The difference between Comparative Example 10 and Example 4 is that the auxiliary agent described in Comparative Example 10 is a single fumed silica.

[0109] Comparative Example 11

[0110] The difference between Comparative Example 11 and Example 4 is that the auxiliary agent described in Comparative Example 11 is a single rosin resin.

[0111] Comparative Example 12

[0112] The difference between Comparative Example 12 and Example 4 is that the ratio of fumed silica and rosin resin in the auxiliary agent is different (not within the scope of the present invention), and the others are the same.

[0113] The auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=0.3.

[0114] Comparative Example 13

[0115] The difference between Comparative Example 13 and Example 4 is that the ratio of fumed silica and rosin resin in the auxiliary agent is different (not within the scope of the present invention), and the others are the same.

[0116] The auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=2.5.

[0117] Test Case

[0118] Test Method

[0119] 1. Appearance test method: For samples after termination / after copper firing, take samples and observe them under a 10x optical microscope to see if there are any abnormalities such as large and small heads or bulges / depressions at the top, and calculate their ratio; observe the top of the samples after copper firing to see if there is any glass overflow or bubbling at the top, and calculate their ratio.

[0120] 2. Statistics of nickel infiltration ratio: Grind the LT surfaces of 50 samples on a metallographic grinder to the 1 / 2 position of the samples. Under the 50x objective mode of a metallographic microscope, observe the distance of the nickel infiltration end and whether it contacts the internal electrode inside the porcelain body.

[0121] 3. Compactness: The copper-sintered sample was solidified in resin, and the LT surface of the sample was ground on a metallographic grinder to the 1 / 2 position of the sample. The compactness of the copper end was observed under a field-induced electromagnetism microscope, and the proportion of the non-dense hole area to the copper end area was calculated.

[0122] The test results are shown in Table 1

[0123] Table 1

[0124]

[0125]

[0126] It can be seen from Table 1 that the conductive copper paste of the present invention solves the problem of bubbling on the side or top of the copper paste end due to the failure to discharge gas in time during sintering, and the appearance problem of cracking at the edge due to excessive sintering shrinkage between copper powder at the edge during sintering, while ensuring good density of the copper end.

[0127] By comparing Example 4 with Comparative Examples 1 and 2, it can be seen that the weight ratio of spherical copper powder and flake copper powder needs to be strictly controlled within the scope of the present invention. If the weight ratio is not within the scope of the present invention, it will cause bubbling problems on the side or top and appearance problems of edge cracking, and the density will also be reduced.

[0128] By comparing Example 4 with Comparative Examples 3 and 4, it can be seen that the present invention selects spherical copper powder and flaky copper powder in a specific weight ratio as the conductive phase, which can more significantly improve the bubbling problem on the side or top and the appearance problem of cracked edges, and also improves the density. If a single spherical copper powder or flaky copper powder is used, either the density is poor, or it will cause bubbling problems on the side or top and the appearance problem of cracked edges, and even nickel infiltration will occur. Therefore, it is necessary to select spherical copper powder and flaky copper powder in a specific weight ratio as the conductive phase of the present invention.

[0129] By comparing Example 4 with Comparative Examples 5 and 6, it can be seen that by controlling the ratio of the conductive copper paste within the scope of the present invention, the bubbling problem on the side or top and the appearance problem of edge cracking can be improved while ensuring good density of the copper end. If the ratio is not within the scope of the present invention, either the density is poor, or it will cause bubbling problems on the side or top and the appearance problem of edge cracking, and even nickel infiltration will occur. Therefore, it is necessary to strictly control the amount of raw materials used in the conductive copper paste.

[0130] By comparing Example 4 with Comparative Examples 7 to 13, it can be seen that the specific ratio of the additives described in the present invention is significant for the density and the bubbling problems on the sides or the top and the appearance problem of edge cracking. The additives composed of fumed silica and rosin resin in a specific ratio are selected to solve the bubbling problem on the sides or the top caused by the failure to discharge the gas in time during the sintering of the copper slurry end, and the appearance problem of edge cracking caused by excessive sintering shrinkage between the edge copper powders during sintering, while ensuring good density of the copper end.

[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A conductive copper paste, characterized in that: The invention comprises the following components in percentage by weight: 65-73% conductive phase, 16-24% organic phase, 8-10% glass phase and 0.8-1% additive; The conductive phase includes spherical copper powder and flake copper powder, and the weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder=1.8-2.5; The auxiliary agent includes fumed silica and rosin resin, and the weight ratio of the fumed silica to the rosin resin is fumed silica:rosin resin=1; The glass phase is at least one of Ba-Si-Zn glass powder, Ba-Zn glass powder, and Si-Zn glass powder.

2. The conductive copper paste according to claim 1, characterized in that: The weight ratio of the spherical copper powder to the flake copper powder is spherical copper powder: flake copper powder=1.8~2.

2.

3. The conductive copper paste according to claim 1, characterized in that: The average particle size of the spherical copper powder is 2-5 μm, and the average particle size of the flake copper powder is 4-9 μm.

4. The conductive copper paste according to claim 1, characterized in that: The glass phase is a Ba-Si-Zn glass powder with a softening point of 450-600° C. and a particle size D50 of 1-3 μm.

5. The conductive copper paste according to claim 1, characterized in that: The organic phase includes resin and solvent, and the weight ratio of the resin to the solvent is resin:solvent=0.3-0.

6.

6. The conductive copper paste according to claim 5, characterized in that: The resin is at least one of acrylic resin, methyl cellulose, ethyl cellulose, polyvinyl butyral, and phenolic resin; The solvent is at least one of terpineol, dihydroterpineol and dihydroterpineol acetate.

7. The conductive copper paste according to claim 6, characterized in that: The resin is acrylic resin.

8. The conductive copper paste according to claim 6, characterized in that: The solvent is terpineol.

9. The method for preparing the conductive copper paste according to any one of claims 1 to 8, characterized in that: The following steps are involved: The conductive phase, the organic phase, the glass phase and the additive are mixed evenly and sieved to obtain a conductive copper paste.

10. Use of the conductive copper paste according to any one of claims 1 to 8 in a multilayer ceramic capacitor.

Citation Information

Patent Citations

  • High-sintering-compactness copper paste for MLCC and preparation method of high-sintering-compactness copper paste

    CN113724912A

  • End-blocking slurry for flaky component

    CN101728002A

  • Plasma display screen barrier slurry and preparation method thereof

    CN102074436A

  • Copper paste and chip multilayer ceramic capacitor

    CN112768110A

  • Conductive paste

    JP2019075231A